DOUBLE STAB EXCISION ARTERIOTOMY-A NOVEL TECHNIQUE FOR A BETTER OUTCOME - Uzair Ahmad; Nauman Imtiaz; Muhammad Irfan; Qurat ul Ain; Farid Ullah Khan; Rizwan Khan (Journal of Ayub Medical College Abbottabad, 2023)
Background: This study was carried out to introduce a new technique of excision arteriotomy and to compare it with standard excision arteriotomy in terms of achieving desired size, shape and margins with minimal technical problems. Methods: This was a comparative study carried out at the Vascular Surgery Unit of Combined Military Hospital Peshawar between January and September 2022. A total of 150 patients of chronic renal failure undergoing Arteriovenous access fulfilling the inclusion criteria were enrolled in our study. The patients were randomized into two groups, 75 in each group: Group A consisted of patients who underwent Conventional excision arteriotomy and Group B underwent Double Stab excision Arteriotomy. The endpoint of the study was to achieve an appropriate arteriotomy of the desired size and shape by having regular margins without intimal dissection during its formation or otherwise inappropriate arteriotomy if any of the criteria is not met. Results: Among the total 150 patients included in our study, Ages ranged between 30-60 years and a mean age of 52.5 years. There were 82 (54.66%) males and 68 (45.33%) females with a male-to-female ratio of 1.2:1. In group A (Conventional Excision arteriotomy) there were 30 (40%) inappropriate arteriotomies and 45 (60%) appropriate arteriotomies. Among the total 30(40%) inappropriate arteriotomies in group A, larger than desired size arteriotomies were 10 cases (33.33%) followed by smaller than desired size arteriotomies; 6 (20%), irregular margins 9 (30%), intimal dissection 3(10%) & lateral tear 2 (6.66%) respectively. In group B of double stab excision arteriotomies, appropriate arteriotomies were achieved in 69 (92%) while the rest had inappropriate arteriotomies in 6 (8%). Among the total 6 (8%) inappropriate arteriotomies in group B, larger than desired size arteriotomies were 2 (33.33%), smaller than desired size arteriotomy; 1 (16.66%), irregular margins 1 (16.66%), intimal dissection; 2 (33.33%) & no lateral tear respectively. Conclusion: This study concluded that the Double stab excision arteriotomy technique is superior to the conventional excision arteriotomy technique. The advantages of our technique are; its reliability with a short learning curve and can be performed precisely and safely.